Kaji Eksperimental Turbin Air Darrieus Tipe-H Menggunakan Blade Hydrofoil Standar Naca 0018 - Arpan Cesar; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The purpose of this study was to experimental study of the Darrieus type H turbine, using NACA 0018standard hydrofoil blade, which variations of 3 blades and 6 blades of turbine diameter of 0.44 m x 0.15 m on theouter turbine and 0.18 x 0.14 m on turbine section with additional of 0.10 m chord length and 0º to 360º attack anglevariations. The variations of velocity flow in water (V) of 0.3 m/s and 0.65 m/s in the water tunnel dimensions of 6 mx 0.6 m x 1 m. The two types of torques were obtained at rest (static torque) for each angle of the azimuth and movingconditions (dynamic torque) from no load and until it stops spinning by utilizing the braking force on the pulley withvariations in loading. In the first test with a variation of 3 blades and the water velocity of 0.3 m/s for the static torquewas obtained 0.288 Nm and a variation of 6 blades of 0.336 Nm. Whilst, a speed of 0.65 m/s static torque generatedat a variation of 3 blades that was 0.36 Nm and a variation of 6 blades of 0.384 Nm for dynamic torque produced 13RPM, which a variation of 3 blades speed of 0.3 m/s and a speed of 0.65 m/ s resulted 23 RPM. The experimentrevealed a variation of 6 blades with a speed of 0.3 m/s at 16 RPM and a speed of 0.65 m/s of 26 RPM. Based on theresults of the study, it can be concluded that the Darrieus hydrokinetic of turbine variation of 6 blades produced moredynamic torque that was compared to the 3 blades variation. It was due to the number of blades greatly influence ofthe kinetic energy absorption of the water to be converted into dynamic and static torques.Keywords: Darrieus turbine, static torque, dynamic torque,NACA 0018